2015
DOI: 10.1039/c4sm02015d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field induced quantum dot brightening in liquid crystal synergized magnetic and semiconducting nanoparticle composite assemblies

Abstract: The design and development of multifunctional composite materials from artificial nano-constituents is one of the most compelling current research areas. This drive to improve over nature and produce 'meta-materials' has met with some success, but results have proven limited with regards to both the demonstration of synergistic functionalities and in the ability to manipulate the material properties post-fabrication and in situ. Here, magnetic nanoparticles (MNPs) and semiconducting quantum dots (QDs) are co-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Visual observations of the switching process through POM did not show any reorientation of the QDs. While the PL emission from quantum rods could be polarized caused by their shape anisotropy, emission from symmetric QDs is expected to be isotropic, and thus the present results appear to be puzzling. It is however noted that the absorption profiles show that the magnitude of absorption is higher in the X configuration than in the Z configuration (See Figure b).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Visual observations of the switching process through POM did not show any reorientation of the QDs. While the PL emission from quantum rods could be polarized caused by their shape anisotropy, emission from symmetric QDs is expected to be isotropic, and thus the present results appear to be puzzling. It is however noted that the absorption profiles show that the magnitude of absorption is higher in the X configuration than in the Z configuration (See Figure b).…”
Section: Resultsmentioning
confidence: 61%
“…A variety of nanoparticles have been employed to alter/tune the LC properties. In fact, QDs have received their fair share of attention in this regard . Presence of QDs has been found to diminish the threshold voltage, accelerate the electro‐optic response, photorefractivity, increase the birefringence, and control PL .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigate the formation and modulation of co-assemblies of Fe 3 O 4 magnetic nanoparticles (MNPs) and CdSe/ZnS core/shell quantum dots (QDs), directed by the thermotropic phase transition of a liquid crystalline (LC) material. This study builds on a prior effort by our group 41 , where we observed the formation of these co-assemblies and demonstrated that a small magnetic field could be used to enhance QDs PL, up to almost three-fold. Simultaneously, the co-assemblies appeared to spatially compress, and from this we indirectly inferred that the clustering of the MNPs produced localized high fields that caused LC re-orientation at low external magnetic fields.…”
Section: Introductionmentioning
confidence: 52%
“…There have been several recent attempts to use liquid crystal defects to assemble and cluster nanoparticles of several types, including semiconducting (e.g., quantum dots), metallic (e.g., gold, silver), and magnetic particles [ 15 ]. Such assemblies may exhibit collective electronic, photonic, or magnetic properties not seen in isolated nanoparticles [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%